Location Suitability Analysis for Wind Farm Exploitation Using Fuzzy Analytic Hierarchy Process - Ade Gafar Abdullah; Almira Hery Setiorini; Nabila Andara Dwitasari; Dadang Lukman Hakim; Muhammad Aziz (Universitas Pendidikan Indonesia, 2021)
The development of renewable energy has been constantly conducted as an attempt to increase energy diversification, improve energy sustainability and reduce greenhouse gas emissions, including the wind power plant (WPP). Suitable location selection is urgently necessary to achieve optimized output and high economic values. There are multi-criteria to be considered during the selection process, namely wind velocity, climate condition, road access, environmental impact, land use, land tilt, plain condition, distance to residential areas, etc. This study aimed to develop a software supporting multi-criteria decision-making based on artificial intelligent technology, namely fuzzy analytic hierarchy process (fuzzy-AHP) which was implemented to evaluate the WPP location suitability. The method of fuzzy-AHP is believed to be able to generate prioritized criteria supporting the location of WPP with high accuracy. Based on those criteria, there were two locations identified at Tanah Laut Regency, South Kalimantan, Indonesia, as the most suitable research sites. It is expected that studies employing fuzzy-AHP are to be further developed to determine wider renewable WPP locations.